Analyzing Cognitive Development in Elementary-Aged Children and Its Implications for Teaching and Learning Strategies - Lestari, Hardita Amalia Sri Ayu; Rinnanik, Rinnanik; Ramadina, Evy; Baiduri, Febi Nur (Jurnal Pendidikan Humaniora, 2023)
The acceleration and optimization of an individual's development can surpass that of their peers, with disparities emerging from age-related, genetic, dietary, and environmental factors. A profound understanding of human development serves as a crucial foundation for comprehending an individual's needs and character, particularly among elementary-aged children. Defined as those aged 7-12 years or encompassed within the educational system, this demographic necessitates a thorough examination of their cognitive development. Cognitive development constitutes an extensive domain that encompasses various thinking abilities, such as reasoning, memory, problem-solving, ideation, and creativity. Consequently, the present study embarks on a substantive and comprehensive analysis of the cognitive development of elementary-aged children, elucidating its implications for pedagogical practices and learning activities within primary educational institutions (SD/MI). The overarching objective of this research is to ascertain the cognitive development levels of children aged 7-12 and beyond, further exploring the subsequent ramifications on teaching materials, strategies, models, and learning methodologies. The anticipated outcomes of this scholarly inquiry are twofold: to augment the existing body of knowledge accessible to the general public and to provide a valuable resource for educators as they fulfill their pedagogical obligations. By investigating the subject matter through a literary or library research approach, this study engages in data collection and information synthesis derived from various sources housed within libraries.